2020
DOI: 10.1128/msystems.00266-20
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and ORF3a: Nonsynonymous Mutations, Functional Domains, and Viral Pathogenesis

Abstract: The effect of the rapid accumulation of nonsynonymous mutations on the pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is not yet known. The 3a protein is unique to SARS-CoV and is essential for disease pathogenesis. Our study aimed at determining the nonsynonymous mutations in the 3a protein in SARS-CoV-2 and determining and characterizing the protein's structure and spatial orientation in comparison to those of 3a in SARS-CoV. A total of 51 different nonsynonymous amino acid subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
261
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(269 citation statements)
references
References 23 publications
4
261
1
3
Order By: Relevance
“…Among the accessory proteins, ORF3a contains six functional domains (I to VI), which may link to viral infectivity, virulence, and ion channel formation (Issa et al, 2020). In a previous study based on 2782 whole-genome sequencing data, it has shown that 51 different non-synonymous amino acid substitutions in the 3a proteins (Issa et al, 2020). Whereas, non-synonymous 25 amino acid substitutions were detected in ORF3a in this study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Among the accessory proteins, ORF3a contains six functional domains (I to VI), which may link to viral infectivity, virulence, and ion channel formation (Issa et al, 2020). In a previous study based on 2782 whole-genome sequencing data, it has shown that 51 different non-synonymous amino acid substitutions in the 3a proteins (Issa et al, 2020). Whereas, non-synonymous 25 amino acid substitutions were detected in ORF3a in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…Although ORF14 was not detected in 184 sequencing data analyzed in this study. Among the accessory proteins, ORF3a contains six functional domains (I to VI), which may link to viral infectivity, virulence, and ion channel formation (Issa et al, 2020). In a previous study based on 2782 whole-genome sequencing data, it has shown that 51 different non-synonymous amino acid substitutions in the 3a proteins (Issa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ORF3a-G171T (Q57H) may affect the formation of ion channels and subsequently influence the viral replication. As for ORF3a-G752T (G251V), a recent analysis predicted that it was in an important functional domain and might be related to virulence, infectivity, ion channel formation and virus release [30]. We also found several important sites for virus entry, though they showed lower substitution frequency in our research data.…”
Section: Discussionmentioning
confidence: 43%
“…The analysis of amino acids frequencies allowed identifying different degree of region conservation throughout the viral genome as a consequence of positive and negative pressures. In particular, nsp3, S, Orf8, and N showed some substitutions in high frequencies.This would indicate, as other authors previously report, the frequent circulation of polymorphisms due to significant positive pressure(Cagliani et al 2020, Issa et al 2020, Tang et al 2020. Additionally, since S and N are among candidates to be used in the formulation of vaccines and antibody treatment, it will be important to monitor these substitutions in different geographic regions in order to improve treatment and vaccination efficacy(Ahmed et al 2020, Callaway, 2020, Koyama et al 2020.…”
mentioning
confidence: 59%